Marsupialization of radicular cysts on adolescent patients to reduce treatment morbidity: a case report - Henri Mudjono; Poerwati S. Rahajoe; Cahya Y. Hasan (Journal of Dentomaxillofacial Science, 2017)
Objective: There are some things that should be considered in treating growing patient with odontogenic cyst. The marsupialization is considered to have more benefits compared to enucleation for growing patient in order to overcome treatment morbidity such as damage to vital structures, heavy loss of bone, jaw growth disturbances, and pathological fracture. This paper reports the success of two cases of marsupialization of odontogenic cysts in order to reduce the treatment morbidity and to discuss about enucleation for young patient.Methods:Two female 21 and 22 years old with radicular cysts on tooth 36. Marsupialization was done before completing cyst enucleation.Results: The shrinkage of the cyst was observed periodically. The position of the wall of the cyst was superficially positioned and the enucleation was done. The treatment result was satisfying with low morbidity.Conclusion:Marsupialization for odontogenic cyst in growing patient has more advantages than enucleation to reduce treatment morbidity.